The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.omtn.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Molecular Mechanism of Peptide-Conjugated Gold Nanoparticle Inhibiting p53-HDM2 Interaction in Retinoblastoma

Abstract: Inhibition of the interaction between p53 and HDM2 is an effective therapeutic strategy in cancers that harbor a wild-type p53 protein such as retinoblastoma (RB). Nanoparticle-based delivery of therapeutic molecules has been shown to be advantageous in localized delivery, including to the eye, by overcoming ocular barriers. In this study, we utilized biocompatible gold nanoparticles (GNPs) to deliver anti-HDM2 peptide to RB cells. Characterization studies suggested that GNP-HDM2 was stable in biologically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…This type of tunable control of the labeling process is critical for the development of systems for the controlled depolarization of membrane potential. More generally, the Chol ligand-based strategy for tethering the AuNPs to the plasma membrane offers benefits not typically afforded by other membrane labeling strategies, such as those that employ peptides or antibodies directed toward specific cell surface receptors. , While in some instances these approaches have been shown to append NPs to the plasma membrane for extended periods of time, they often result in rapid endocytosis and cellular internalization of the NPs . The Chol ligand used herein, however, appends the AuNPs with extended membrane residence that enables an experimental window for controlled depolarization studies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This type of tunable control of the labeling process is critical for the development of systems for the controlled depolarization of membrane potential. More generally, the Chol ligand-based strategy for tethering the AuNPs to the plasma membrane offers benefits not typically afforded by other membrane labeling strategies, such as those that employ peptides or antibodies directed toward specific cell surface receptors. , While in some instances these approaches have been shown to append NPs to the plasma membrane for extended periods of time, they often result in rapid endocytosis and cellular internalization of the NPs . The Chol ligand used herein, however, appends the AuNPs with extended membrane residence that enables an experimental window for controlled depolarization studies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Alternatively, another inorganic-based therapeutic approach developed and established the use of AuNPs to deliver anti-HDM2 (human double minute 2) to Y79 cells. 320 HDM2 is an oncogene that is overexpressed in many cancers including retinoblastoma. 321,322 Findings of this study revealed that the designed nanosystem decreased survival of Y79 cells by inhibiting cell proliferation, promoting apoptosis through the PUMA-BCL2-BAX axis, and activating the cell proliferation checkpoint.…”
Section: Perspectives Of Inorganic-based Nanocarriers In the Manageme...mentioning
confidence: 99%
“…However, they have limited applications owing to their toxicity [130][131][132]. To address these concerns, Kalmodia et al (2017) developed green synthesis methodology for the synthesis of gold nanoparticles (GNPs) using extracts of Vitus vinifera [133]. The GNPs synthesized were biocompatible and noncytotoxic.…”
Section: Gold Nanoparticles (Aunps)mentioning
confidence: 99%